2015
DOI: 10.1007/s11096-015-0085-4
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ perception of generic substitution in Iran

Abstract: In conclusion, the trust of Iranian's society on the physicians and pharmacists advice would create a credible opportunity to reduce pharmaceutical expenditures as well as patients' out of pocket by promotion of generic substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Keenum et al 22 have observed that most participants agreed that generic drugs were cheaper (98%), were as effective as the reference medicine (77%), and reported not caring about the replacement (80%); but only 45% said they preferred generic drugs over brand name drugs 22 . This may be due to some prior negative experiences or guidance received from the prescriber 36 . This is similar to our finding that 18% of those who do not prefer generic drugs end up replacing the prescribed drug by the equivalent generic drug.…”
Section: Discussionmentioning
confidence: 99%
“…Keenum et al 22 have observed that most participants agreed that generic drugs were cheaper (98%), were as effective as the reference medicine (77%), and reported not caring about the replacement (80%); but only 45% said they preferred generic drugs over brand name drugs 22 . This may be due to some prior negative experiences or guidance received from the prescriber 36 . This is similar to our finding that 18% of those who do not prefer generic drugs end up replacing the prescribed drug by the equivalent generic drug.…”
Section: Discussionmentioning
confidence: 99%
“…1 Consequently, pharmaceuticals, as an important component of the health system, have dramatically increased the cost of health care systems. 2 Moreover, the cost of pharmaceutical products has rapidly grown in recent years owing to the higher cost of production as well as research & development (R&D). Indeed, the expenditure of pharmaceutical products has become a challenging issue for governments and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on decisions made by pharmacists and patients, pharmacists in Iran can legally substitute generics for brand name drugs, but such substitution is not mandatory [7]. In recent years in Iran, total health expenditures increased, but the public sector share of pharmaceutical expenditures decreased [8]; the increasing trend of the use of brand name drugs has led to an increase in patients' out-of-pocket expenses to [60 % of total health costs [9].…”
Section: Introductionmentioning
confidence: 99%